The abundance and diversity of antibiotic resistance genes in layer chicken ceca is associated with farm enviroment - Xiao, Shasha; Mi, Jiandui; Chen, Yingxin; Feng, Kunxian; Mei, Liang; Liao, Xindi; Wu, Yinbao; Wang, Yan (Frontiers in Microbiology, 2023)
Industrialized layer chicken feedlots harbor complex environmental microbial communities that affect the enrichment and exchange of gut bacteria and antibiotic resistance genes (ARGs). However, the contribution of different environmental sources to the gut ARGs of layer chickens is not clear. Here, layer chicken gut and environmental samples (air, water, feed, cage, feather, maternal hen feces, uropygial glands) were collected during the early 3 month period before the laying of eggs, and the source and characteristics of the gut microorganisms and ARGs were analyzed by performing 16S rRNA and metagenomic sequencing. The results showed that the abundances of Bacteroidetes and Actinobacteria in cecum of layer chickens gradually increased, while that of Proteobacteria decreased with age, and the number and relative abundance of ARGs decreased significantly with age. On day 5, 57% of the layer chicken cecal ARGs were from feather samples, and 30% were from cage samples. Subsequently, the contribution of cage ARGs became progressively more prominent over time. At days 30 and 57, the contribution of cage ARGs to the chick cecal ARGs reached 63.3% and 69.5%, respectively. The bacterial community composition (especially the abundances of Klebsiella pneumoniae and Escherichia coli) was the major factor impacting the ARG profile. K. pneumoniae and E. coli were mainly transmitted from feathers to the layer chicken cecum, and the contribution rates were 32% and 3.4%, respectively. In addition, we observed the transmission of ARG-carrying bacteria (Bacteroides fragilis) from the cage to the gut, with a contribution rate of 11.5%. It is noteworthy that B. fragilis is an opportunistic pathogen that may cause diarrhea in laying hens. These results can provide reference data for the healthy breeding of layer chickens and the prevention and control of ARG pollution.